Unexploited Thapsia garganica, Orlaya maritima, and Retama raetam Seeds: Potential Sources of Unsaturated Fatty Acid and Natural Antioxidants. (27th June 2015) - Tlili, Nizar; Mejri, Houda; Lajnef, Houda Ben; Feriani, Anouer; Khaldi, Abdelhamid; Nasri, Nizar
Abstract: Total lipid contents, fatty acid compositions, phenolic profiles and antioxidants activities of seeds from Thapsia garganica, Orlaya maritima, and Retama raetam were investigated. The oil values were more than 26 %, except seeds of R. raetam (ca. 3 %). Unsaturated fatty acids accounted for the majority of the fatty acids (more than 75 %). Oleic and linoleic acid were the predominant fatty acids. Total phenolic compounds (24–104 mg GAE g −1 DR), total flavonoids (4–102 mg QE g −1 g DR), total tannins (28–85 mg GAE g −1 DR) and condensed tannins (0.62–131 mg CE g −1 DR) were also determined. The antioxidant activities using different assays were evaluated. The predominant detected classes were the phenolic acids (42–85 %) and the flavonoids (11–48 %). The major phenolic acids were caffeic, trans ‐4‐hydroxy‐3‐methoxycinnamic, p ‐coumaric, and gallic acid. The predominant flavonoids were quercetin, luteolin, naringin, apigenin, and kaempferol. This study brings attention to the medicinal importance of these species as a source of oil and antioxidant molecules.